Identification of Potential Donors for superior fruit quality traits and genes for resistance to tomato leaf curl virus (ToLCV) In tomato and allied species - Nadkarni Siddhesh Raghvehdra (Department of Plant Breeding and Genetics, College of Agriculture, 2017)
The study entitled ‘‘Identification of potential donors for superior fruit quality traits and genes for resistance to tomato leaf curl virus (ToLCV) in tomato and allied species’’ was conducted during the period 2014-2017, in the Department of Plant Breeding and Genetics, Vellayani with an objective of evaluating varieties and allied species of tomato for fruit quality traits and genes for resistance to ToLCV through biochemical analysis and molecular markers and to study compatibility for hybridization and seed set to transfer ToLCV genes to bacterial wilt resistant variety ‘’Anagha’’ from donors of related species. Thirty-four genotypes including allied species of tomato were collected from different sources and studied under four different experiments. First experiment was screening of thirty-four genotypes under natural field condition for tomato leaf curl virus resistance in summer season and scoring for ToLCV by the scale given by Banerjee and Kalloo (1987). Eight genotypes viz., EC 541109 (Solanum pimpinellifolium L.) EC 168283 (Solanum pimpinellifolium L.), IIHR1970 (Solanum peruvianum L.) and LA 2805 (Solanum lycopersicum var. cerasiforme L.), IIHR 2372, IIHR 2200, Vaibhav and Nandi were found to be highly resistant. The scions of these eight highly resistant genotypes were grafted on susceptible root stock with ToLCV symptoms. The scions did not take symptoms after 25 days confirming the resistance of the genotypes. Evaluation of thirty-four genotypes for yield and fruit quality parameters was carried out in field condition during rabi season. The analysis of variance revealed significant difference for all seventeen quantitative and fruit quality attributes. On the basis of mean performance for different yield characters, genotypes viz., Vaibhav, EC 320574, EC 165751, EC 164656 and EC 16786 were superior, whereas genotypes EC 541109, IIHR 2372, Vaibhav and LA 2805 were superior for fruit quality traits. The wild species used in the study had high content of carotene, lycopene and TSS. From coefficient of variation it was evident that the estimates of GCV were higher than the corresponding PCV for all seventeen quantitative attributes indicating the less influence of environment on the expression of these genotypes. The estimates of GCV and PCV were higher for seven characters indicating the existence of high variability in the material studied offering ample scope for selection. Heritability estimates and genetic advance as per cent of mean (GAM) were high for all characters indicating predominance of additive gene action for these characters. Phenotypic and genotypic correlation coefficient analysis with respect to weight of fruits per plant-1 showed positive significant correlation with plant height, number of primary branches plant-1, spread of the plant, number of days to 50% flowering, number of days to first fruit harvest, number of fruits plant-1, weight of fruit and volume of fruit. Path analysis confirmed that direct effect on number of fruits plant-1 expressed highest positive direct effect on weight of fruits plant-1, followed by weight of fruit, spread of the plant, lycopene content, number of primary branches plant-1, number of days to 50% flowering and number of days to first fruit harvest. Molecular markers linked to the three genes Ty2, Ty3 and Ty3a specific to ToLCV resistance were validated with thirty-four genotypes. Genotypes IIHR 2200, Vaibhav and EC168283 (Solanum pimpenellifolium L.) showed the presence of Ty2 gene and genotype IIHR 1970 (Solanum peruvianum L.) showed the presence of Ty3a gene. The identified resistant lines were crossed with ‘‘Anagha’’ the popular bacterial resistant variety with an objective to transfer the resistance. All the seven successful hybrid combinations showed 100% pollen fertility confirming the compatibility of the parents. Evaluation of seven hybrids with parents revealed significant difference for all seventeen quantitative and fruit quality attributes. On the basis of mean performance for different yield and fruit quality traits in hybrids viz., L1 x T1 (Anagha x Vaibhav) showed superiority for characters like weight of fruits plant-1, weight of fruit, volume of fruit, pH of juice and shelf life, L1 x T5 (Anagha x EC 541109) showed superiority for characters like plant height, number of primary branches, lycopene content, TSS %, and carotene content, L1 x T2 (Anagha x Nandi) showed earliness in number of days to 50% flowering and number of days to first fruit harvest, L1 x T4 (Anagha x IIHR 2372) showed superiority for traits like pericarp thickness and vitamin C. Seven hybrids were screened and scored for ToLCV, in natural field conditions. Highly resistant reaction was found in four hybrids viz., L1 x T3 (Anagha x EC 168283), L1 x T5 (Anagha x EC 541109), L1 x T6 (Anagha x IIHR 2200), L1 x T7 (Anagha x LA 2805). This study could identify resistance sources for ToLCV viz., EC 541109, EC 168283, IIHR1970, LA 2805, IIHR 2372, IIHR 2200, Vaibhav and Nandi. The genotypes Vaibhav, EC 320574, EC 165751, EC 164656, EC 16786, EC 541109, IIHR 2372 and LA 2805 which showed superiority in yield and fruit quality traits can be used for breeding for improvement of yield and quality traits. The wild species which are found compatible with cultivated species can be used as donors for quality traits as well as resistance. The hybrid L1 x T1 (Anagha x Vaibhav) with superior yield traits and resistance to ToLCV can be recommended for release after yield trials. Hybrid L1 x T5 (Anagha x EC 541109) an interspecific hybrid with superior fruit quality traits can be recommended for release as cherry tomato after trials. The segregating population of interspecific crosses can be used for further evaluation to locate plant types with good yield, fruit quality along with resistance to ToLCV.